Research Progress on the Anti-Liver Cancer Mechanism and Toxicity of Rhubarb Anthraquinone - Yu L; Qin J; Zhang M; Gao Y; Zhao Y (Drug Design, Development and Therapy, 2024)
Linyuan Yu,1,2 Jinxing Qin,2 Mei Zhang,3 Yawen Gao,4 Yongli Zhao1 1Department of Pharmacy, Chengdu Integrative TCM & Western Medicine Hospital, Chengdu, Sichuan, 610095, People’s Republic of China; 2Department of Pharmacy, Sichuan Second Hospital of T.C.M, Chengdu, Sichuan, 610031, People’s Republic of China; 3Department of Neurosurgery, Guiqian International General Hospital, Guiyang, Guizhou, 550000, People’s Republic of China; 4Department of Anesthesia, Southwest Medical University, Luzhou, Sichuan, 646000, People’s Republic of ChinaCorrespondence: Yongli Zhao, Chengdu Integrative TCM & Western Medicine Hospital, No. 18, Wanxiang North Road, Gaoxin District, Chengdu, 610095, People’s Republic of China, Email lipingyaoshi0851@163.comEthnopharmacological Relevance: Rhubarb has the effect of breaking blood stasis and abnormal mass, and was often used to treat various tumor diseases including liver cancer in ancient China. Recipes containing rhubarb have anti-liver cancer properties and are still used today. However, the main components and mechanism of action of rhubarb against liver cancer are still unclear.Aim of the Review: To conduct a review of the anti-liver cancer effects and toxicity of rhubarb anthraquinones (AQs).Materials and Methods: This article reviewed the effects of rhubarb AQs in the treatment of liver cancer and the signaling pathways involved, and discussed the toxicity and pharmacokinetics of rhubarb AQs by searching the Web of Science, PubMed and CNKI databases.Results: Rhubarb (Rhei Radix et Rhizoma) is a traditional Chinese medicine that has been existed for thousands of years and is used as an anti-cancer drug. Modern pharmacological research shows that rhubarb AQs, as the main component of rhubarb, contains emodin, rhein, chrysophanol, physcione and aloe-emodin, which has anti-liver cancer effects and can be considered as a potential therapeutic drug for liver cancer. However, many modern studies have shown that rhubarb AQs have certain toxicity, which hinders in-depth research on rhubarb AQs.Conclusion: Rhubarb AQs can be used as a potential anti-liver cancer drug, but its research still has many limitations. Strengthening research on related experiments and finding a balance between toxicity and efficacy are all directions worth studying in the future. Keywords: rhubarb anthraquinone, liver cancer, toxicity, pharmacokinetics